2010
DOI: 10.1152/ajpgi.00252.2009
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating effects and mechanisms of electroacupuncture on gastric dysrhythmia, delayed emptying, and impaired accommodation in diabetic rats

Abstract: The aim of this study was to investigate the effects and mechanisms of electroacupuncture (EA) on gastric accommodation, gastric dysrhythmia, and gastric emptying (GE) in streptozotocin (STZ)-induced diabetic rats. Five experiments were performed in five groups of STZ-induced diabetic rats to study the effects of EA at ST-36 (Zusanli) on gastric slow-wave dysrhythmia, delayed GE and intestinal transit, impaired gastric accommodation, and the mechanisms of EA involving the autonomic and opioidergic pathways. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
133
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 94 publications
(135 citation statements)
references
References 55 publications
(74 reference statements)
2
133
0
Order By: Relevance
“…EA reduced high sympathetic nerve activity in women with polycystic ovary syndrome (45). In animal models and humans with gastrointestinal motility disorders, EA was shown to increase vagal activity and reduce sympathovagal balance (34,40,48). On the basis of these previous findings, a possible autonomic mechanism is hypothesized: EA improves vagal activity and suppresses sympathetic activity, leading to a reduction in free fatty acid and improvement in insulin sensitivity.…”
Section: Discussionmentioning
confidence: 92%
“…EA reduced high sympathetic nerve activity in women with polycystic ovary syndrome (45). In animal models and humans with gastrointestinal motility disorders, EA was shown to increase vagal activity and reduce sympathovagal balance (34,40,48). On the basis of these previous findings, a possible autonomic mechanism is hypothesized: EA improves vagal activity and suppresses sympathetic activity, leading to a reduction in free fatty acid and improvement in insulin sensitivity.…”
Section: Discussionmentioning
confidence: 92%
“…More Met-enkphalin was released with EA at 2 Hz, whereas, more dynorphin was released with EA at 100 Hz (8,16). In GI motility studies, the commonly used stimulation frequency for EA ranged from 10 to 25 Hz: EA at 10 Hz/25 Hz was found to increase gastric motility in rats (17,52,53), and EA at 25 Hz accelerated liquid gastric emptying and enhanced antral contractions in dogs (7,34). In this study, EA was performed at 25 Hz, and the findings were consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…EA at ST36 restored rectal distentioninduced impairment in gastric slow waves in dogs and increased the spikes in rabbits. [35][36][37] EA at ST36 improved the percentage of normal gastric slow waves as well as the percentage of tachygastria in healthy volunteers. 38 Liu et al 21 reported that 2-week TEA at ST36 decreased dyspepsia symptoms and elevated vagal activity in patients with functional dyspepsia.…”
Section: Discussionmentioning
confidence: 90%